Prevalence of Antibody to Current Influenza Virus Strains in a 1992 Canadian Serosurvey and Crude Estimates of 1991–92 Season A/Beijing/353/89 Infections - John M Weber (Canadian Journal of Infectious Diseases)
Objectives: The annual influenza serosurvey was conducted to monitor influenza activity and gauge susceptibility to currently circulating and emerging influenza viruses.